Case report: STRN3-NTRK3 fusion in uterine sarcoma with spleen metastasis: a new variant in the spectrum of NTRK-rearranged tumors - Colombo, Piergiuseppe; Buonamassa, Giuseppina Adriana; Giulianini, Anita; Hassan, Letizia; Rudini, Noemi; Rizzo, Antonio; Cavallo, Enrico; Carnaghi, Carlo; Goudarzi, Salumeh; Mongiovì, Sebastiano; Pafumi, Sarah; Marletta, Stefano (Frontiers in Medicine, 2024)
Neurotrophic tyrosine receptor kinase (NTRK) fusions are infrequent genetic events that can occur in various tumor types. Specifically, NTRK-rearranged sarcoma has been observed in pediatric mesenchymal tumors and, to a lesser extent, in adult mesenchymal tumors like fibrosarcoma. Recently, NTRK-rearranged uterine sarcoma (US) has been identified as a rare entity characterized by constitutive activation or overexpression of the TRK receptor, which plays a role in cell proliferation and differentiation. Since its initial description in 2018, only 46 cases of NTRKrearranged US have been reported. In this context, herein we describe an exceptional case of an STRN3::NTRK3 fused US with histologically confirmed splenic metastasis. Notably, such localization has not been previously associated with pure uterine sarcomas in the literature. The fusion involved STRN3 (exon-3) and NTRK3 (exon-14) genes and was identified through next-